OPTIMALISASI AKUNTANSI HIJAU DALAM PENGEMBANGAN STRATEGI PENJUALAN UMKM KERUPUK KULIT KAMPUNG BARU - Dania Gita Cahyani (Prodi Akuntansi, Universitas Pamulang Kampus Serang, 2025)
This study aims to optimize the application of green accounting in the development of sales strategies for MSMEs of Kerupuk Kulit in Kampung Baru, Serang City. Green accounting, which emphasizes recording and reporting environmental costs, is integrated with sales strategies to improve the environmental and economic performance of MSMEs. Through qualitative and participatory research methods, data is collected through interviews, observations, and analysis of company documents, namely by making participants contribute to the activities carried out . The results show that the implementation of green accounting can help Kerupuk Kulit MSMEs in identifying and reducing the environmental impact of their production activities. In addition, a sales strategy that focuses on environmental value is proven to increase competitiveness and customer loyalty. The implementation of green accounting also shows operational cost efficiency and improved corporate image in the eyes of consumers who are increasingly concerned with environmental issues. This study suggests that other MSMEs in Serang City and the surrounding region adopt green accounting as part of a sustainable business strategy to achieve economic benefits while preserving the environment.This community service activity was carried out on May 8, 2024 at Jl. Kp. Baru, Panancangan, Kec. Cipocok Jaya, Serang City, Banten and was attended by 21 local people. Optimizing green accounting in developing sales strategies for leather cracker MSMEs in Kampung Baru, Serang City, is a very important step to improve business sustainability and efficiency. Hopefully, this community service activity can improve operational efficiency, reduce negative impacts on the environment, and attract consumers who are increasingly concerned about sustainability. This not only benefits the environment, but can also improve brand image and open up new market opportunities.